Eficiencia de desinfección en piscinas de clima tropical: caso de estudio parque acuático piscilago, girardot - Colombia. (2018)
This research is based on the comparison of the effectiveness of the three disinfection methods used in the pools of the Mega Park (Chlorine, Ozone and UV Radiation); by means of the characterization of the water of a total of ten (10) pools, taking into account the physicochemical and microbiological parameters; For this purpose, the samples taken by the Park between the months of August 2016 and December 2017 and two counter samplings in the months of June and September 2018, carried out by the researcher, are analysed in order to verify the pattern between the different dates and the influence of the season (high or low), defined by the affluence of the public and finally, to determine the main advantages and disadvantages of each method. However, chlorine, due to its molecular stability, continues to disinfect even after it has been applied. Therefore, ozone and UV radiation methods receive a minimum dose of chlorine to guarantee the residual effect; on the other hand, these processes are difficult to access due to their high cost of acquisition and operation, so they are only used in parks with the economic capacity to finance this type of treatment.